Pie-Crusting Technique of Medial Collateral Ligament for Total Knee Arthroplasty in Varus Deformity: A Systematic Review - Motififard, Mehdi; Ravanbod, Hadi; Rahmati, Rashed; Saleki, Mohammad (Advanced biomedical research, 2023)
We aimed to better understand the outcomes/complications of pie-crusting technique using blade knife during total knee arthroplasty (TKA) in patients with knee genu varum deformity. A systematic search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. English and Persian language articles were considered on the use of pie-crusting technique during TKA in patients with knee genu varum/varus deformity using related keywords and Medical Subject Headings terms with reported postoperative complications and outcomes. Primary search resulted in 81 studies of them 9 included in our study (ages ranged: 19 years to 62 years). No perioperative complications and/or any significant differences between pie-crusting and control group were observed. Except for two studies that found no significant positive effect for the use of pie-crusting, other studies found pie-crusting a useful and promising technique. Four studies found significant improvement in pie-crusting group compared to control in terms of functional Knee Society Score (KSS), range of motion (ROM), medial gap, and the knee-specific KKS. Three records found no significant differences in terms of functional KSS, ROM; however, they reported fewer use of constrained inserts or a reasonable correction of femoral tibial angle. No serious complications were reported. Due to the inconsistency of the results on the efficiency and outcomes of pie-crusting, we cannot make a firm conclusion and more high-quality studies are needed in this regard. However, this method can be considered as a safe method which depends on the skill of surgeon.